Bioactivity evaluation of nanosized ZnFe2O4 fabricated by hydrothermal method - Hangai, Bruno [UNESP]; Acero, G. [UNESP]; Ortega, Pedro Paulo [UNESP]; Garcia, Filiberto G.; Simoes, Alexandro Z. [UNESP] (Univ Novi Sad, Fac Technology, 2021)
In this study, we investigated the structural, microstructural, magnetic and cytotoxic properties of encapsulated ZnFe2O4 nanoparticles. The nanoparticles were synthesized using the microwave-assisted hydrothermal method and their surfaces were silanized and later encapsulated with poly-2-hydroxyethyl methacrylate (PHEIVIA). Due to the compatibility of Zn2+ ions with a human body, ZnFe2O4 nanoparticles are preferable among all kinds of ferrites for biomedical applications. Quantitative phase analysis obtained by the Rietveld refinement reveals the formation of a single-phase spinel cubic structure. Magnetic hysteresis loops measured at 2 and 300 K reveal a remanent magnetization of 4.427 emu/g and 1.002 emu/g, respectively. Such behaviour was ascribed to change in the inversion degree of the spinel structure. The experimental g-factor (g = 1.897) obtained using electron paramagnetic resonance analysis can be attributed to the microwave heating, which induces more surface-active oxygen species. In addition, we demonstrated that the encapsulated ZnFe2O4 nanoparticles showed an absence of cytotoxicity at concentrations of 1.0, 10 and 20 mu g/ml against human embryonic kidney (HEK) cells since no significant changes in cell morphology were observed. Hence, our results indicate the possibility to explore the use of ZnFe2O4 nanoparticles encapsulated with PHEIVIA for biomedical applications, such as cancer therapies.
Keywords: nanopowders; microwave processing; magnetic properties; electronic paramagnetic resonance